The Effect of Legislated Tax Changes on the Trade Balance: Empirical Evidence for the United States, Germany, and the United Kingdom - Bernd Hayo; Sascha Mierzwa (Philipps-University Marburg, School of Business and Economics, 2021)
Using a narrative account of quarterly discretionary changes in tax liabilities from 1974Q4 to 2018Q2 in a VAR setting, we study whether legislative tax changes affect the trade balance in the United States, Germany, and the United Kingdom. As legislative tax changes we consider (i) all changes, (ii) personal income tax changes, (iii) business tax changes, (iv) indirect tax changes in Germany and the UK, (v) spillovers of US tax changes into Germany and the UK, and (vi) asymmetric reactions after tax hikes and cuts. Generally, we find that after a reduction in aggregated tax liabilities, imports and exports in the US and Germany react quite similarly: imports tend to rise; exports do not change much. Consequently and fostered by growing output—the net-exports-to-GDP ratio decreases. We find no clear net effect in the UK. Instead, UK imports only increase after cuts to indirect taxes. However, employing normal variations of the tax changes as a yardstick, the economic magnitude of the estimated effects on the trade variables is not particularly large. Thus, there remain doubts as to whether tax policy is an effective instrument for addressing trade imbalances.
Keywords: E62; F41; H30; K34; 330; Fiscal policy; tax policy; legislated tax changes; trade balance; exports; imports; Germany; United Kingdom; United States; VAR; narrative approach